Neurocognitive Functions and Behavior in Joubert Syndrome - Andrea Poretti; Gwendolyn J. Gerner (Pediatric Neurology Briefs)
Investigators from multiple Italian pediatric neurology and neurogenetics departments studied cognitive functions, behavior, and adaptive functioning in large cohort of 54 patients with Joubert syndrome (JS) as part of a prospective, multi-center study.